A SOCIOLINGUISTIC HISTORY OF BRITISH ENGLISH LEXICOGRAPHY - Yong, Heming; Peng, Jing (London ; New York : Routledge, 2021)
"A Sociolinguistic History of British English Lexicography traces the evolution of British English dictionaries from their earliest roots to the end of the 20th century by adopting both sociolinguistic and lexicographical perspectives. It attempts to break out of the limits of the dictionary-ontology paradigm and set British English dictionary making and research against a broader background of socio-cultural observations, thus relating the development of English lexicography to changes in English, accomplishments in English linguistics, social and cultural progress, as well as advances in science and technology. It unfolds a vivid, coherent and complete picture of how English dictionary making develops from its archetype to the prescriptive, the historical, the descriptive and finally to the cognitive model, how it interrelates to the course of the development of a nation's culture and the historical growth of its lexicographical culture, and how English lexicography spreads from British English to other major regional varieties through inheritance, innovation and self-perfection. This volume will be of interest to students and academics of English Lexicography, English Linguistics and world English lexicography"--
Includes bibliographical references and index.
Keywords: English language -- Great Britain -- Lexicography -- History; Encyclopedias and dictionaries -- Great Britain -- History and criticism